Rancang Bangun Sistem Informasi Pengolahan Nilai Berbasis Web di SMK Al-Farisi Leles - Silvia Julianti; Topan Trianto; Heri Purwanto (Jurnal Dimamu, 2023)
SMK AL-Farisi Leles is a private school in the Garut district. The activities in the processing of grades are still using Microsoft Excel and Microsoft Word and then submitted to the homeroom teacher for inclusion in the report card of each student. This takes more time for the homeroom teacher to get the grades of each student subject because each teacher has a different schedule in the school. A website of information system design is a step taken to design a program using a website, which is a collection of several pages that are interconnected with other interconnected files to facilitate a process in an organization; in this case, we design a value-processing information system at SMKS Al-Farisi. It is known that some of the information needed to create a value processing information system is curriculum information, academy year, major, homeroom teacher, student, lesson, and the student's own grades. The value processing information system at SMK Al-Farisi Leles serves to facilitate the processing of grades, starting from the input process to making student value reports so that they can be managed effectively and efficiently. The design of this information system can streamline the time of the homeroom teacher in viewing student grade results without having to wait for Microsoft files from the teacher of each lesson. There is no need for a process of synchronizing grades by the homeroom teacher because the grades have been automatically caught by the system and can be accessed by students without limited space and time, so that students can see the value of learning outcomes anywhere and anytime.